2013
DOI: 10.1111/jasp.12191
|View full text |Cite
|
Sign up to set email alerts
|

A theory‐driven investigation of prospective applicants' intentions to submit video résumés

Abstract: As a quickly growing trend among job seekers, video résumés represent an area where practice has outpaced research. This study investigated whether the theory of planned behavior (TpB) can be used to understand future job seekers (n = 154) video résumé submission intentions and behaviors. Results supported the TpB model. Attitudes, subjective norms, and perceived behavioral control predicted intentions, which in turn predicted video résumé creation behaviors. Compared with perceived behavioral control, attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Video resumes are a growing trend in the job application process, and have received a substantial amount of media attention in Europe and in the United States (Gissel, Thompson, & Pond, ). More organizations are offering online resume posting sites with multimedia capabilities, allowing job applicants the option of submitting a video resume to replace or supplement a traditional written resume (Dizik, ), and a recent international study found that 70% of experienced Human Resource (HR) professionals were familiar with video resumes (Hiemstra, Derous, Born, & Serlie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Video resumes are a growing trend in the job application process, and have received a substantial amount of media attention in Europe and in the United States (Gissel, Thompson, & Pond, ). More organizations are offering online resume posting sites with multimedia capabilities, allowing job applicants the option of submitting a video resume to replace or supplement a traditional written resume (Dizik, ), and a recent international study found that 70% of experienced Human Resource (HR) professionals were familiar with video resumes (Hiemstra, Derous, Born, & Serlie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Op internet en in andere, populaire media is er veel te vinden over video cv's (Gissel, Thompson & Pond, 2013). Een bekend voorbeeld van werving en selectie waarbij video cv's werden gebruikt, is een grote wervingscampagne die in 2009 werd gestart in Australië.…”
Section: Video Cv'sunclassified
“…The increased use of technology and Internet in screening procedures () has resulted in the emergence of so‐called ‘video resumes.’ Video resumes are videotaped messages in which applicants present themselves to potential employers (). The popularity of video resumes is reflected in an increasing use of and media attention to video‐based applications, both in the United States and Europe (; ). Instead of merely turning paper‐and‐pencil resumes into videotaped versions, multimedia allows applicants to actually show their knowledge, skills, abilities, and other characteristics (e.g., interpersonal competencies) that may be difficult to capture with traditional paper resumes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a growing number of companies are offering services that range from online hosting of video resumes in search databases for recruiters, to the full production of resumes for applicants. A search conducted by ) for the keywords ‘video résumés’ on popular web sites yielded 10,900 hits on YouTube.com and 49,300,000 on google.com. Since then, it appears that the topic has only gained popularity in the popular press and media, which contrasts with the paucity of published empirical research in the Web of Science ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation